Ritualism (dis)order: street carnivals, transgression and excesses in Nigeria (2014)
Carnival as an annual event has transcended numerous culture. A number of studies have principally investigated the intended economic, entertainment and/or leisure components of carnivals; neglecting the unintended social, moralistic and behavioural consequences it has on society. This study therefore examines the social vices associated with street carnivals in selected neighbourhoods. Major narratives revealed that nudity, sex, gambling, fanaticism, hooliganism, alcohol and drug abuse were major reoccurring challenges facing street carnivals in Lagos. It was also observed that the concentration of youths on weekends around football viewing centres (FVCs) contributed to the high wave of violence during carnivals. Similarly, the impact of globalisation and acculturation of foreign ideas and behaviours into street carnival was described as negative on youth and adolescent. Data for the study were collected through observations and in-depth interviews with residents and organizers of street carnivals in Lagos State, Nigeria.